Capital market and economic growth in Nigeria - Keji Sunday Anderu (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
The objective of this study is to empirically examine the nexus between capital market and economic growth in Nigeria between 1980 and 2017. In the cause of pursuing the desired result, the economic growth was proxy by the gross domestic product (GDP) while the capital market variables considered included market capitalization, all shares index, number of dealings, gross capital formation, exchange rate, value of all transaction and interest rate. This study is predated by the ineffectiveness of capital market which affects liquidity, acquisition of information about firms such as risk diversification, savings harmonization and corporate management. In lieu of this, the research adopted Auto-regressive Distribution Lag model and Bound Cointegration Testing. The results revealed that there is long run relationship between capital market and economic growth in Nigeria. To justify the findings, post estimation tests were conducted. For instance, the Jarque-Beta test suggest that the residuals for both models are normally distributed since the probability value is greater than 5% significant level. Hence, the hypothesis of normal distribution for residuals cannot be rejected. The Breusch-Godfrey Serial Correlation (LM) test re-affirms that the hypothesis of no autocorrelation can be rejected since the probability value is greater than 5% critical value. Henceforward, the study recommends that government should expand the market technological based in order to further improve transactions and dealings, which could enhance its internationalization and competitiveness. Also, regulatory body like security and exchange commission (SEC) should improve its supervisory roles towards reducing shoddy and unethical dealings in the Nigerian capital market